Hypertension and Dysentery in Family Medicine : A Case Report - Setijowati, Nanik; Cendhani, Cinantya (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2026)
Hypertension and dysentery are two common health problems encountered in primary care, especiallyin elderly patients. This case report presents a 68-year-old patient with a history of hypertension anddysentery, managed within the framework of family medicine. The management approach includedpharmacological, non-pharmacological, family, and environmental interventions. This case highlightsthe crucial role of family physicians in addressing biological, psychological, social, andenvironmental aspects of patient care.